THE IMPACT OF RELOCATION FROM SLUM TO SIMPLE RENTED FLATS ON THE HEALTH OF RESIDENTS AT KAMPUNG PULO - Pebrianto Syafruddin; Isbandi Rukminto Adi (Politeknik Kesejahteraan Sosial Bandung, 2019)
This research discussed the impact of relocating from Kampung Pulo in East Jakarta that was exposed to the environment by the local government of the capital (DKI) Jakarta due to their initial condition occupying the slums on the Ciliwung River were often affected by flooding when the rainy season. The research also illustrated the impact of relocation on the health of Kampung Pulo residents in their environment, health facilities and reality they perceived. This research was a qualitative study presented descriptively. The results stated that there were changes, namely changes that occurred in the health condition of Kampung Pulo residents, when the flood felt the mud entered into their homes and the threat of diseases such as diarrhea, vomit and skin diseases aggravated by the condition of unavailability of sanitation, such as the availability of toilets and water needs and could be seen that many of their homes di not have such facilities. But after the relocation they got excellent sanitation and water proved in each unit of flats had a lavatory, raw water that can be cooked to be used to cook and drink, a sink as well as a clean and separate cooking place, other than that. This research could also see that the health level of Kampung Pulo residents increased, they were not suffering from any disease as suffered at Kampung Pulo, a fundamental change in their health.